Annotated checklist and key to the species of amphibians and reptiles inhabiting the northern Peruvian dry forest along the Andean valley of the Marañón River and its tributaries - Koch, Claudia; Venegas, Pablo J.; Cruz, Roy Santa; Böhme, Wolfgang (Zootaxa, 2018)
A checklist of the amphibians and reptiles of 35 localities situated in the northern Peruvian dry forest valley of the Marañón River and its tributaries, containing 14 species of amphibians and 54 species of reptiles, is provided from data collected between July 2005 and April 2014 during several herpetological surveys and from the literature. Detailed accounts are given for each collected species containing morphometric and scalation data, information on natural history, comments regarding their distribution, the conservation status and key literature. Eleven new species were discovered and described during the survey period. At least five additional taxa might also represent new species but more field work and data collection are necessary to determine their status. For two snake species we provide the first country record and for 23 further species new departamental records are provided.